Optimization of ADV sampling strategies using DNS of turbulent flow - Gil Montero, Vicente Gastón (2014)
This work presents an investigation on the effects of spatial and temporal averaging processes (filtering) implemented in an Acoustic Doppler Velocimeter (ADV) on the computations of the turbulent kinetic energy, velocity variances, and Reynolds shear stresses. The averaging processes are implemented in the ADV technology in order to reduce the noise level inherent in acoustic measurements. A conceptual model, simulating the ADV operation and the turbulent flow field, is developed to assess the filtering effects on the turbulence parameter estimates of sampling volume heights, recording frequencies, and distances from the sampling volume to the channel bottom. The results of the conceptual model are compared with experimental data. The findings provide a criterion to examine the capability of ADV to characterize turbulent flows using different sampling configurations.